Laozi Belief and Taoism in the Western Regions—An Analysis with a Focus on the Cultural Strategy of the Han and Tang Dynasties for the Western Regions - Jiamin Si; Jishao Han (Religions)
The spread of Taoism to the Western Regions marked the movement of Central Plains culture to the frontier, demonstrating its influence on local society. During the Han Dynasty, Central Plains culture had reached the Western Regions. With the deification of Laozi and his becoming the founder of Taoism, the story “Laozi converting the barbarians” (Laozi huahu 老子化胡), which claimed that Laozi journeyed to the west and taught the Hu people, provided the impetus for the spread of Taoism to the Western Regions. The Tang imperial family venerated Laozi and regarded Taoism as the state religion. Laozi belief, including the veneration of the man himself, his writings, his stories, and the precepts claimed to be related to him, was also used to assist in the Tang Dynasty’s governance of the Western Regions. Following the Tang Dynasty’s decline, the Central Plains’ influence receded from the Western Regions. However, due to the relaxed religious environment in the Western Regions, Taoism, which was representative of Central Plains culture, still survived there. Moreover, Taoism attempted to incorporate Islam in the Western Regions into its divine system by huahu, which might be related to the early history of exchange between the two religions.